THE EFFECT OF DIVIDEND POLICY AND FINANCIAL PERFORMANCE ON COMPANY VALUE WITH THE DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY AS A MODERATION VARIABEL: (Case Study of Food and Beverage Sub Sector Companies on the Indonesia Stock Exchange, Malaysia Exchange, and Singapore Exchange in 2019-2021) - Bambang Sugiharto; Dhea Dinda Meliana (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The purpose of this study was to examine the effect of dividend policy and financial performance on company value with corporate social responsibility as a moderating variabel. This study uses a population of food and beverage sub sector companies on the Indonesia Stock Exchange, Malaysia Exchange, and Singapore Exchange in 2019-2021. The sample determination method used was purposive sampling, the sample used in the study was as much as 139 data. The methote of determining the hypothesis testing used in this study uses multiple regression analysis and moderating regression analysis. The result show that dividend policy have not effect on company value, while liquidity ,leverage and profitability has a positive effect on company value, and activity has a negative effect on company value. Meanwhile, corporate social responsibility is only able to moderate the effect of liquidity, leverage, and profitability on company value and is unabell to moderate the effect of dividend policy and activity on company value. And there are difference in the value of companies listed on the Indonesia Stock Exchange, Malaysia Exchange, and Singapore Exchange in 2019-2021.